Effects of ZnO-Based Smart Urea Coating on Ammonium Release and Characterization of Soil Ureolytic Bacteria in Loamy Soil - Fathia Meidy Nurindriana; M. Wasilul Lutfi; Atiqah Aulia Hanuf; Soemarno Soemarno; Sugeng Prijono (The University of Lampung, 2026)
The application of ZnO-coated urea is a promising strategy to reduce nitrogen losses and improve zinc availability in soils. This study aimed to evaluate the effects of ZnO-coated urea on soil ammonium concentrations and ureolytic bacterial populations. A completely randomized design was used with five treatments:control (CU), uncoated urea (CU) and ZnO-coated urea at three different coating (bulk ZnO (NCU-Z), ZnO NPs (NCU-ZNP), and ZnO NPs combined with bentonite NPs (NCU-ZBNP)), each with four replications. Soil samples were incubated on sterile jars under controlled conditions for 8 weeks and used loamy soil as a medium. Ammonium concentrations were measured using the spectrohotometry, while ureolytic bacteria were enumerated using the total plate count (TPC). NCU characterization results revealed inconsistencies in coating thickness, however, it has shown significant results on soil ammonium content and total ureolytic bacteria population. Results on the number of ureolytic bacterial populations showed that NCU-ZNP treatment could reduce the number of bacteria up to 77.8%. The research results also showed that the NCU-ZBNP treatment significantly maintained soil ammonium levels that were 1.76 times higher compared to CU.These findings suggest that ZnO-coated urea can slow nitrogen transformation and potentially improve nitrogen use efficiency while influencing soil microbial communities.